Personalized Liquid Biopsy May Predict Relapse in Aggressive Endometrial Cancer. (9th November 2022) - Harris, F; McCune, A; Murphy, S; Smadbeck, J; Ali, M; Penheiter, A; Karagouga, G; Sadeghian, D; Cucinella, G; Mariani, A; Vasmatzis, G
Abstract: Introduction/Objective: High-grade endometrial cancer (EC) recurs in 50% of patients following surgery and first-line chemotherapy. There are no established blood-based biomarkers with sufficient specificity and sensitivity to monitor EC patients for residual disease and recurrence. The ability to detect and monitor EC currently relies on serial imaging based approaches. Liquid biopsies via blood-based tests for cell-free circulating tumor DNA (ctDNA) are becoming increasingly popular, but none have been FDA approved for EC and current approaches have not been validated in patients with uncommon tumor mutations. We hypothesized that personalized testing panels based on tumor-specific chromosomal rearrangements would allow ctDNA to be monitored and that ctDNA presence correlates with other clinical indicators of recurrence. Methods/Case Report: Twelve patients with FIGO Stage I-IV and biopsy confirmed high-grade EC were prospectively enrolled and underwent primary tumor resection. DNA was isolated from tumor tissue and sequenced on Illumina NGS platforms [San Diego, CA]. BIMA algorithm and SVAtools identified junctions of somatic chromosomal rearrangements and 4-5 junctions were chosen per patient, based primarily on copy number/amplification level. Blood was collected before surgery, and longitudinally between 1 and 7 timepoints. Total cell-free DNA (cfDNA) was extracted from platelet poor plasma with the Qiagen CNA kit [Germany]. Personalized ctDNA qPCR Taqman [IDT, Coralville, Iowa] probe assays were developed with pooled pre-amplification to maximize sensitivity for the multiple junctions and normalized to input. Results (if a Case Study enter NA): ctDNA was detected in 9/12 and 5/12 cases pre- and post-surgery, respectively. The detection or absence of measurable ctDNA following surgery showed high correlation with cancer recurrence as detected by CT or MRI scans. Conclusion: The detection of ctDNA in high-grade EC using personalized junction panels shows promise for a blood-based assay that may help physicians better monitor and treat patients.